Acute Toxicity Bioassay Of Desmodium Molliculum (H.B.K.) D.C. Manayupa - Gordillo, Gloria (2019)
Objective: To evaluate acute oral toxicity by the method of the decoction classes of the aqueous extract of leaves and stems of Desmodium molliculum (H.B.K.) D.C., manayupa (EAM), at a maximum concentration of 2000 mg / kg body weight. Biological material: Leaves and stems of Desmodium molliculum, manayupa and Mus musculus strain Balb / c / CNPB, adult male and female mice. Methodology: The leaves and stems of Desmodium molliculum, manayupa collected in La Encañada-Cajamarca were desiccated and crushed to 1.5 mm, subjected to a hot aqueous extraction, filtered and concentrated by lyophilization. The acute oral toxicity study was performed using doses of 500, 1000 and 2000 mg / kg bw, respectively. The observations made were recorded that were aimed at the determination of: signs and symptoms of toxicity, weight, death and time of occurrence of the same on days 1, 7 and 14. Results: Under the conditions of the trial, the manayupa did not produce manifestations of symptoms indicative of toxicity, or mortality in mice, no significant changes in body weight were observed. Conclusions: The oral administration for 14 days of the aqueous extract of leaves and stems of Desmodium molliculum (HBK) DC, manayupa, at concentrations up to 2000 mg / kg bw of Mus musculus strain Balb / c / CNPB, mice, is not toxic and it is framed between the “unclassified” substances in the animal model and the dose level used under the experimental conditions observed.